1993
DOI: 10.1007/bf01202738
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological status of rabbit carcases in Egypt

Abstract: A total of 40 New Zealand white rabbits, 20 freshly slaughtered rabbits from an experimental farm and 20 processed rabbit carcases from grocery stores in Beni-Suef city, were examined bacteriologically. The mean values of aerobic plate counts at 37 degrees C and 1 degrees C, Enterobacteriaceae counts, Pseudomonas counts and Staphylococcus counts of freshly slaughtered rabbits were 10(4) +/- 2 x 10(3), 8 x 10(2) +/- 10(2), 6 x 10(2) +/- 10(2), 3 x 10(2) +/- 10(2), and 10(2) +/- 60 organisms per gram respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 12 publications
6
10
0
Order By: Relevance
“…So that slaughtered rabbit carcasses generally have low bacterial count when slaughtered under high sanitary conditions, while during handling and processing the number of microorganisms increased significantly. Moreover, these reports are in accordance with the conclusion of Khalafalla (1993) that slaughtered rabbit carcasses from the groceries stores have higher bacterial counts than home slaughtered.…”
Section: Apc At 35 °Csupporting
confidence: 89%
See 2 more Smart Citations
“…So that slaughtered rabbit carcasses generally have low bacterial count when slaughtered under high sanitary conditions, while during handling and processing the number of microorganisms increased significantly. Moreover, these reports are in accordance with the conclusion of Khalafalla (1993) that slaughtered rabbit carcasses from the groceries stores have higher bacterial counts than home slaughtered.…”
Section: Apc At 35 °Csupporting
confidence: 89%
“…It was found that it ranged from 5.1×10 3 to 8.8×10 6 , 3.9×10 3 to 9.3×10 6 , 2.6×10 3 to 9.3×10 6 and 5.1×10 3 to 4.0×10 6 , with mean values accounted for 1.5×10 6 , 1.1×10 6 , 1.2×10 6 and 5.7×10 5 CFU/g flesh in shoulder, loin, rib and thigh regions, respectively. Slightly higher results were recorded by Abou-Taleb (1995) and Hohn (1960), while approximately similar values were obtained by Shiffman (1961) and Sunki et al (1978), and lower values were reported by Comin et al (2008) and Khalafalla (1993). From the data illustrated in Table (2), it could be concluded that the MPN of coliforms in examined rabbit meat samples ranged from <3 to 1.5×10 4 , <3 to 9.3×10 3 , <3 to 1.5×10 4 and 7.4 to 9.3×10 3 , with mean values of 2.0×10 3 , 1.2×10 3 , 1.7×10 3 and 1.7×10 3 microorganisms/g meat in shoulder, loin, rib and thigh regions, respectively.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…For frozen thighs from Argentinian hare, Hoppe (1981) reported a range of 3 to 5 log cfu/g, and Türck (2008) reported a median of 3.7 log cfu/g (range of 2.2 to 6.2 log cfu/g). It is important to note that hunted hares are not necessarily more contaminated than slaughter animals of similar size, e.g., mean values of 4-5 log cfu/g for slaughtered farmed rabbits are reported by several studies conducted on different continents (Khalafalla 1993;Bobbitt 2003;Rodriguez-Calleja et al 2004). Initial EB counts were 2.2±0.3 and 2.7±0.2 log cfu/g (n= 10) for categories "A" and "B", respectively.…”
Section: Development Of the Microflora And Phmentioning
confidence: 95%
“…Similarly, to meat of other food animals intended for human consumption, rabbit meat should be free from any microbiological hazards. Different types of bacterial pathogens are nevertheless sporadically detected in raw rabbit meat (Khalafalla 1993;Pyz-Łukasik and Szkucik 2005).…”
Section: Introductionmentioning
confidence: 99%